(untitled) (Journal of the College of Basic Education, 2024)
Hospital are one of the Urban landmarks , such as Mosques , Hospice , Domes and Schools , that Muslims built and made lots of endowments on it , and it was one its fruits was that Islamic medical sciences developed through their establishment and they made medical care in hospitals a right for all members of Islamic society , This prompted them to seek the help of many non – Muslim doctors and benefit from the system , Hospitals existed in their countries , Hospitals spread throughout the Islamic world , and their development of medical profession .